CHILDFREE AGREEMENT IN THE PERSPECTIVE OF MEDAN CITY ULAMA - Intan Lubis; Nurul Huda (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study aims to explain the Childfree Agreement in the Ulama Perspective of Medan City. According to the Islamic religion, marriage is something noble and sacred which is one of the muamalah which has the value of worshiping Allah and carrying out the sunnah of the Prophet. Childfree marriage, namely marriage with the husband and wife's agreement and agreement not to have children during the marriage. The method used in this research is normative legal research method. The formulation of the problem that will be discussed in the research, What is meant by Chlidfree, How is the Agreement of Ulama of Medan City towards Childfree. The results of the study note that childfree or childless marriage agreements are seen in the principles of Islamic symbols, until now there has been no argument against not having a child in marriage, but it is recommended by religion to have a child, in this regard the Medan city clerics took one of a source explaining about Childfree written by Sheikh Syauqi Ibrahim Alam from Dar Ifta Egypt, issued a fatwa number 4713, 5 February 2019 regarding the presence of offspring in the family. First, in Islam there is no statement in the Qur'an or Hadith that obliges husband and wife to have children. Second, there is an agreement between husband and wife not to have children. The reason is, being a parent is not a trivial thing, there is a big responsibility. Third, the unwillingness to have children, according to Sheikh Ibrahim Alam, is analogous to the case of azal or termination of intercourse before reaching an orgasm so that the husband's sperm comes out outside the wife's vaginal opening. the view of Medan city scholars is that it is permissible to practice Childfree, because until now there is no argument or one text (Al Ashlu) which clearly prohibits a husband and wife from not having a child and in Al ibahah that it is permissible for a husband and wife to choose between doing or not making an agreement to have children in marriage, and is only limited to a recommendation to have a child so that the case can be seen from Islamic law maslahah mursalah which means regardless or free from information indicating whether Childfree is permissible or not. marriages that practice Chlidfree do not have texts (Al Ibahah) or arguments that clearly prohibit not having a child in marriage, but what is recommended by religion to have a child. Keywords : Childfree, Ulama's perspective, Marriage Law